1978
DOI: 10.2307/1128756
|View full text |Cite
|
Sign up to set email alerts
|

Family Interaction in Abusive, Neglectful, and Normal Families

Abstract: This study represents an attempt to discover whether there are distinctive patterns of day-to-day interactions that distinguish abusive and neglectful families from families with no known history of abusing or neglecting their children. Observational data collected in the homes of 17 abuse, 17 neglect, and 19 control families indicated that the abusive and neglectful parents demonstrated lower rates of interaction, overall, and were more likely to emphasize the negative in their relationships with their childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
171
4
4

Year Published

1980
1980
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(193 citation statements)
references
References 0 publications
14
171
4
4
Order By: Relevance
“…For example, studies of maltreating mothers suggest that the emotional and expressive environments they provide for their children deviate in important ways from normal experience (Camras, Sachs-Alter & Ribordy, 1996). Abusive parents engage in fewer positive emotional interactions with their children than nonabusive parents (Burgess & Conger, 1978) and direct more negative affect toward their children than nonmaltreating mothers (Trickett, Aber, Carlson, & Cicchetti, 1991). Although maltreated children are generally poorer at recognizing emotions (Camras et al, 1990), the experience of physical abuse may increase children's attention to anger (Pollak, Klorman, Thatcher, & Cicchetti, 2001).…”
Section: The Emotion Learning Environment and The Development Of Percmentioning
confidence: 99%
“…For example, studies of maltreating mothers suggest that the emotional and expressive environments they provide for their children deviate in important ways from normal experience (Camras, Sachs-Alter & Ribordy, 1996). Abusive parents engage in fewer positive emotional interactions with their children than nonabusive parents (Burgess & Conger, 1978) and direct more negative affect toward their children than nonmaltreating mothers (Trickett, Aber, Carlson, & Cicchetti, 1991). Although maltreated children are generally poorer at recognizing emotions (Camras et al, 1990), the experience of physical abuse may increase children's attention to anger (Pollak, Klorman, Thatcher, & Cicchetti, 2001).…”
Section: The Emotion Learning Environment and The Development Of Percmentioning
confidence: 99%
“…Moreover, the prevalence of such children is increasing and creates a need that far exceeds available personnel and resources (President's Commission on Mental Health, 1978). The need to help families with conduct-problem children is particularly important because studies have shown that these children are at an increased risk not only for being abused by their parents (Burgess & Conger, 1978;Patterson, 1977: Reid, Taplin, & Loeber, 1981 but also for developing psychiatric disabilities as adults, particularly those evidenced by juvenile delinquency and crime (Loeber, 1985;Patterson, 1974;Robins, 1978Robins, , 1981Rutter & Geller, 1983).…”
mentioning
confidence: 99%
“…Abused children are more likely than are matched controls to engage their mothers in coercive interactions (Burgess & Conger, 1978;Reid, Taplin, & Lorber, 1981) and to display aggressive behavior toward siblings, peers, or other adults (George & Main, 1979;Lewis, Shanok, Pincus, & Glaser, 1979;Snyder, 1977).…”
mentioning
confidence: 99%